Description of Teacher's Knowledge and Attitudes to Individual Learning Program - Arta, Artafanti (Indonesian Journal of Disability Studies, 2018)
The learning of the Sekolah Luar Biasa (SLB) focused on the diversity of abilities and potential of students. This need can be facilitated by modifying the curriculum based on assessment of students, which is then used as the basis for making the Program Pembelajaran Individu (PPI). The study was conducted on Jakarta SLBN X teachers who began to modify the curriculum, but were not yet maximal. The study uses quantitative methods with qualitative data as supporting data. Quantitative data was obtained through measuring instruments of knowledge and attitudes towards the making of PPIs filled by 29 teachers. While qualitative data was obtained through interviews with nine teachers based on the results of quantitative data categorization (lacking, sufficient, good). The results showed that 34% had insufficient knowledge, 59% were sufficient, and 7% were good about making PPIs. While 45% of teachers have a lack of attitude and are quite positive, and 10% of teachers are categorized as good in their attitude towards making PPIs. Different tests show there are differences in the attitudes of teachers who have and have never attended workshops on handling students with special needs. Qualitative data shows that the factors that play a role in making PPI are lack of knowledge of teachers in making PPIs, regulations in schools that have not required the making of PPIs, and lack of time to prepare PPIs.